Comprehensive comparative efficacy and safety of potent P2Y12 inhibitors in patients undergoing coronary intervention: A systematic review and meta-analysis - Chien-Lung Huang; Tien-Ping Tsao; Wei-Hsian Yin; Wen-Bin Huang; Hsu-Lung Jen; Chang-Chyi Lin; Chung-Yi Chang; Ching-Hwa Hsu (International Journal of Cardiology: Heart & Vasculature, 2024)
Potent P2Y12 receptor antagonists have been used widely for patients undergoing percutaneous coronary intervention with different results. Benefits from different regimens various between trials. Randomized controlled trials (RCTs) have restrictive inclusion and exclusion criteria; thus, they may limit the generalizability of the findings to a broader population. This study was aimed to comprehensively investigate the outcomes of potent P2Y12 inhibitors in patients undergoing PCI, including RCTs and real-world evidence (RWE) studies.Multiple electronic databases were systemically reviewed and searched on compared potent P2Y12 inhibitors with clopidogrel. The primary efficacy end point was composite ischemic cardiovascular event and primary safety endpoint was major bleeding. Overall estimates of proportions and incidence rates with 95 % confidence intervals (CI) were calculated using fixed-effects models. Total 24 studies (140,986 patients) underwent coronary intervention were included in this meta-analysis, including 18 RCTs and 6 large cohort studies with propensity score matching. The potent P2Y12 inhibitors including cangrelor, prasugrel, and ticagrelor, significantly decreased the risk of composite adverse cardiovascular ischemic events (95 % CI 0.89–0.96, p < 0.001), but increased major bleeding (95 % CI 1.15–1.33, p < 0.001) or any bleeding (95 % CI 1.21–1.33, p < 0.001) compared with Clopidogrel.This meta-analysis merges RCTs and RWE studies and comprehensively evidences newer potent P2Y12 inhibitors are significantly more effective than clopidogrel in reduction of composite adverse thrombotic events, but the incidence of major or any bleeding was higher compared with clopidogrel.